A phosphine mediated sequential annulation process of 2-tosylaminochalcones with MBH carbonates to construct functionalized aza-benzobicyclo[4.3.0] derivatives. Issue 28 (23rd March 2017) - Zhang, Qinglong; Zhu, Yannan; Jin, Hongxing; Huang, You
Abstract : A novel phosphine mediated sequential annulation process to construct functionalized aza-benzobicyclo[4.3.0] derivatives has been developed involving a one-pot process. Abstract : A novel phosphine mediated sequential annulation process to construct functionalized aza-benzobicyclo[4.3.0] derivatives has been developed involving a one-pot sequential catalytic and stoichiometric process, which generates a series of benzobicyclo[4.3.0] compounds containing one quaternary center with up to 94% yield and 20 : 1 dr value. In this reaction, MBH carbonates act as 1, 2, 3-C3 synthons.